Analisis Penerapan Model Discovery Learning dalam Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran Biologi - Asrinawati, Asrinawati; Kayla Fatimah Zulfah; Selestina Rebacca Sihotang; Tafrijiyah Hasanah; Ade Suryanda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The choice of student learning models significantly influences student learning results, underscoring the importance for educators to employ models that align with the content being taught. One such model is Discovery Learning, particularly applicable in the field of biology. This approach guides students toward conclusions by fostering an understanding of concepts, meanings, and relationships through intuitive processes. The aim of this research is to evaluate the efficiency of applying the Discovery Learning model in the field of biology education by analyzing the educational results following its implementation. The research methodology involves a literature review as part of the descriptive analysis approach. The findings from the literature review indicate that employing the model of Discovery Learning with or without additional media and learning strategies, positively affects the biology learning objectives of students. The discernible enhancement in student performance in Biology following the implementation of the Discovery Learning model substantiates its effectiveness. In summary, based on the insights derived from the literature review, the use of the Discovery Learning approach to biology instruction has been found to be helpful in improving student learning results.